Non-linearities in passive RFID systems third harmonic concept and applications - Andía, Gianfranco; Duroc, Yvan; Tedjini, Smaïl (Focus series, 2018)
This book concerns a new paradigm in the field of UHF RFID systems: the positive exploitation of nonlinear signals generated by the chips integrated into the RFID tags